2006
DOI: 10.1097/01.brs.0000248453.51165.0b
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Atrophy of the Lumbar Multifidus Follows Experimental Disc or Nerve Root Injury

Abstract: These data resolve the controversy that the multifidus cross-sectional area reduces rapidly after lumbar injury. Changes after disc lesion affect 1 level with a different distribution to denervation. Such changes may be due to disuse following reflex inhibitory mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
267
2
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 344 publications
(291 citation statements)
references
References 61 publications
9
267
2
3
Order By: Relevance
“…Although we were only able to identify a significant relationship between multifidus density and spondylolisthesis when we used the summative measure from the principle component analysis, when data were considered separately for each level we identified an association between muscle density of multifidus and/or erector spinae at a specific lumbar level and FJOA, disc narrowing, and spondylolisthesis and related levels. This is consistent with data of Hides [16], and Hodges [17] following acute pain/ injury and Danneels [6] in chronic LBP, L4 multifidus density was reduced in association with FJOA or spondylolisthesis at L4-5. As multifidus fibers arising from L4 arise from the caudal border of the spinous process and adjacent lamina [38], their bulk lies adjacent to L5.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although we were only able to identify a significant relationship between multifidus density and spondylolisthesis when we used the summative measure from the principle component analysis, when data were considered separately for each level we identified an association between muscle density of multifidus and/or erector spinae at a specific lumbar level and FJOA, disc narrowing, and spondylolisthesis and related levels. This is consistent with data of Hides [16], and Hodges [17] following acute pain/ injury and Danneels [6] in chronic LBP, L4 multifidus density was reduced in association with FJOA or spondylolisthesis at L4-5. As multifidus fibers arising from L4 arise from the caudal border of the spinous process and adjacent lamina [38], their bulk lies adjacent to L5.…”
Section: Discussionsupporting
confidence: 92%
“…They proposed that the wasting was not likely to be due to disuse atrophy because of the rapidity of onset and localized distribution. Animal studies have shown atrophy to develop rapidly after experimental injury to an intervertebral disc [17]. Again these changes were localized to the level of injury and were associated with rapid changes in intra-muscular fat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence from humans and animal models, including ovine 58, porcine 59, 60, and feline 61 that induced local injury compromises neural drive to the MF, seen as changes in electrical activity on MF electromyography. Experimentally induced intervertebral disc degeneration in the cat induces pathophysiologic changes to the MF 62.…”
Section: Introductionmentioning
confidence: 99%
“…However, changes in spinal mechanics have been reported as a common element (Panjabi, 2006). Altered spinal mechanics and LBP have been linked with atrophy (Hides et al, 2008a;Danneels et al, 2000;Hodges et al, 2006;Hodges & Richardson, 1996;Ferriera et al, 2004) and altered motor control (Hodges & Richardson, 1996) of the lumbar multifidus (LM) and transversus abdominis (TrA) muscles. Atrophy of LM and TrA has also been associated with loss of lordosis, development of back pain and spinal injury, and following periods of low activity and disuse of spinal muscles (Buckey, 2006;Hides et al, 2011;Sayson & Hargens, 2008).…”
Section: Introductionmentioning
confidence: 99%